2012
DOI: 10.1029/2012gl051884
|View full text |Cite
|
Sign up to set email alerts
|

Delayed deglaciation or extreme Arctic conditions 21‐16 cal. kyr at southeastern Laurentide Ice Sheet margin?

Abstract: [1] The conventionally accepted ages of the Last Glacial Maximum (LGM) retreat of the southeastern Laurentide Ice Sheet (LIS) are 26-21 cal. kyr (derived from bulk-sediment radiocarbon ages) and 28-23 cal. kyr (varve estimates). Utilizing accelerator mass spectrometry (AMS) 14 C dating of earliest macrofossils in 13 lake/bog inorganic clays, we find that vegetation first appeared on the landscape at 16-15 cal. kyr, suggesting ice had not retreated until that time. The gap between previous age estimates and our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(45 citation statements)
references
References 40 publications
1
43
1
Order By: Relevance
“…An exception to this argument is the basal date on the Minnewaska core, which gives the onset of organic deposition at 17,360-17,917 cal yr BP. This date appears to be in conflict with regionally younger ages for deglaciation and forest arrival based on plant macrofossils (Peteet et al, 2012) and may reflect mixing of older organics contained within clastic sediments derived from glacial tills with younger organics produced by lacustrine primary producers and leaf litter.…”
Section: Age Controlmentioning
confidence: 85%
“…An exception to this argument is the basal date on the Minnewaska core, which gives the onset of organic deposition at 17,360-17,917 cal yr BP. This date appears to be in conflict with regionally younger ages for deglaciation and forest arrival based on plant macrofossils (Peteet et al, 2012) and may reflect mixing of older organics contained within clastic sediments derived from glacial tills with younger organics produced by lacustrine primary producers and leaf litter.…”
Section: Age Controlmentioning
confidence: 85%
“…In Switzerland, for example, Andree et al (1986) found an 800-year offset in radiocarbon age between bulk sediment and AMS plant macrofossil ages for the late-glacial interval, while offsets of up to 8 ka occur in basal lake sediments in central North America (Grimm et al, 2009). In another example, the initiation of 13 lakes/bogs across a landscape previously covered by the south-eastern LIS provided a tight cluster of AMS ages between 16 and 15 ka (Peteet et al, 2012), which is 5-9 ka later than the time of ice retreat based upon the extrapolation of bulk chronologies (Dyke et al, 2003), varves (Ridge, 2004), and cosmogenic dates (Balco et al, 2009). …”
Section: Radiocarbon Dating and Pan-ice Sheet Margin Chronologiesmentioning
confidence: 99%
“…et al, 2001Ridge, 2004) offer a seemingly precise chronology for icesheet retreat through that sector. However, as argued by Borns et al (2004) and later by Peteet et al (2012), these essentially "floating" chronologies are pinned to the calendar time scale in relatively few locations (see below), raising the possibility of systematic age offsets in the deglacial record. Thus, much of the chronology of ice-sheet retreat in New England is known only on a first-order basis.…”
Section: Introductionmentioning
confidence: 97%